Aoteasalda and Kiwisaldula, two new genera of Saldidae (Hemiptera: Heteroptera), with a key to New Zealand genera and a new synonymy in Zemacrosaldula - Larivière, Marie-Claude; Larochelle, André (Zootaxa, 2016)
Aoteasalda new genus, is described with Saldula maculipennis Cobben, 1961, as type species, resulting in the following new combination Aoteasalda maculipennis (Cobben, 1961). Kiwisaldula new genus, is described with Saldula parvula Cobben, 1961, as type species. The following new combinations are made: Kiwisaldula parvula (Cobben, 1961); Kiwisaldula butleri (White, 1878); Kiwisaldula laelaps (White, 1878); Kiwisaldula stoneri (Drake & Hoberlandt, 1950). Two species are described as new: Kiwisaldula manawatawhi new species, Kiwisaldula porangahau new species. A lectotype is designated for Salda laelaps White, 1878. The holotype of Salda butleri White, 1878, and the type series of Saldula trivialis Cobben, 1961, and Saldula maculipennis Cobben, 1961, are documented. A new synonymy is established in the genus Zemacrosaldula (valid name listed after equal sign): Saldula trivialis Cobben, 1961 = Zemacrosaldula australis (White, 1876). A revision of the taxonomy of Aoteasalda and Kiwisaldula species occurring on New Zealand’s North Island and nearby offshore islands, is presented. Morphological descriptions are provided, with illustrations emphasising the most significant diagnostic features of the external morphology and male genitalia. Information is given on synonymy, type data, material examined, geographic distribution, and biology. Species of Kiwisaldula and genera of Saldidae recognised for New Zealand, are keyed.